Studies of three dimensional stagged-grid finite difference for Z-axis tipper electromagnetic numerical simulation - Wang, Yu; Qu, Junhao; Chen, Tingting; Zhou, Shaohui; Li, Yajun (Frontiers in Earth Science, 2025)
ZTEM (Z-Axis Tipper Electromagnetic System) is a frequency-domain airborne electromagnetic exploration method that utilizes natural field sources. This method is highly efficient and capable of probing great depths, making it widely applicable in the exploration of polymetallic mineral deposits. However, large-scale 3D forward modeling faces computational challenges due to the increase in data volume. This study employs the Aggregation-based Algebraic Multigrid (AGMG) and staggered grid finite-difference methods to achieve rapid solutions for three-dimensional ZTEM problems. The study shows that the AGMG-CG algorithm requires fewer iterations and achieves faster solutions, significantly enhancing computational speed, especially for large-scale 3D forward modeling problems. By analyzing the forward response characteristics of ZTEM, we show that tipper data accurately reflect lateral electrical interfaces. Furthermore, through extensive model testing, we analyze the main factors influencing the forward response of ZTEM. The study reveals that topographical variations may produce false anomalies, that a reasonable data acquisition bandwidth is crucial for identifying anomalies at different depths, and that low-altitude flights yield better responses.